Catheter ablation in patients with persistent atrial fibrillation - Kirchhof, Paulus (Eur Heart J, 2017)
Catheter ablation is increasingly offered to patients who suffer from symptoms due to atrial fibrillation (AF), based on a growing body of evidence illustrating its efficacy compared with antiarrhythmic drug therapy. Approximately one-third of AF ablation procedures are currently performed in patients with persistent or long-standing persistent AF. Here, we review the available information to guide catheter ablation in these more chronic forms of AF. We identify the following principles: Our clinical ability to discriminate paroxysmal and persistent AF is limited. Pulmonary vein isolation is a reasonable and effective first approach for catheter ablation of persistent AF. Other ablation strategies are being developed and need to be properly evaluated in controlled, multicentre trials. Treatment of concomitant conditions promoting recurrent AF by life style interventions and medical therapy should be a routine adjunct to catheter ablation of persistent AF. Early rhythm control therapy has a biological rationale and trials evaluating its value are underway. There is a clear need to generate more evidence for the best approach to ablation of persistent AF beyond pulmonary vein isolation in the form of adequately powered controlled multi-centre trials.